2013
DOI: 10.1002/grl.50502
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic sulfate aerosol and the southward shift of tropical precipitation in the late 20th century

Abstract: [1] In this paper, we demonstrate a global scale southward shift of the tropical rain belt during the latter half of the 20th century in observations and global climate models (GCMs). In rain gauge data, the southward shift maximizes in the 1980s and is associated with signals in Africa, Asia, and South America. A southward shift exists at a similar time in nearly all CMIP3 and CMIP5 historical simulations, and occurs on both land and ocean, although in most models the shifts are significantly less than in obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
206
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(238 citation statements)
references
References 39 publications
23
206
2
Order By: Relevance
“…Some of them also focus on anthropogenic factors, such as climate change, aerosol emissions, land use practices and resulting land-atmosphere interactions, contributing to drought inducing mechanisms (e.g. Dai, 2011Dai, , 2013Hwang et al, 2013;Lebel et al, 2009;Zeng, 2003). The review of these studies revealed that there are a number of factors contributing to inducing drought conditions.…”
Section: Causes Of Droughtsmentioning
confidence: 99%
“…Some of them also focus on anthropogenic factors, such as climate change, aerosol emissions, land use practices and resulting land-atmosphere interactions, contributing to drought inducing mechanisms (e.g. Dai, 2011Dai, , 2013Hwang et al, 2013;Lebel et al, 2009;Zeng, 2003). The review of these studies revealed that there are a number of factors contributing to inducing drought conditions.…”
Section: Causes Of Droughtsmentioning
confidence: 99%
“…Subsequently, however, this cold and dry anomaly is advected into Asia, where it induces atmospheric and surface feedbacks over Asia and the Western North Pacific (WNP), which also weaken the EASM. In spite of very different perturbations to the local aerosol burden in response to Asian and European sulphur dioxide 1 3 , decadal changes in sensible heat flux over the Tibetan Plateau (Ding et al 2009;Duan et al 2013), anthropogenic aerosol (Xu 2001;Menon et al 2002;Huang et al 2007;Liu et al 2009Liu et al , 2011Chen et al 2012;Zhang et al 2012;Guo et al 2013;Hwang et al 2013;Jiang et al 2013;Ye et al 2013;Wang et al 2013;Zhou et al 2013;Polson et al 2014;Song et al 2014), and natural decadal variability (Lei et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We concentrate on meridional mean change because a substantial literature on zonal mean change and its relationship to aerosol forcing and interhemispheric energy budget imbalance already exists (e.g., Yoshimori and Broccoli 2008;Scheff and Frierson 2012;Chiang et al 2013;Hwang et al 2013) and because GCM-simulated response is more obviously connected with asymmetries in surface properties caused by zonal variations in land fraction than in the zonal mean case. (We do make zonal mean results and maps available in the online supplemental information for reference.)…”
mentioning
confidence: 99%